Looking at DAI NIPPON's Footprint: Japan's Policies in Indonesia - Febriana Khoiriyah; Zulkarnain Zulkarnain; Ardian Fahri (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2023)
The purpose of this study is to identify the policy of the Japanese government system in Indonesia. The method adopted in this study is the historical method, which consists of four stages, namely, heuristics, source criticism, interpretation, and historical historiography, as well as techniques of data collection through literature research. According to the studies carried out, it can be seen that many political changes took place during the Japanese occupation of Indonesia, especially the abolition of the discrimination system and other measures in the military, government and educational sectors. However, all the moves and policy changes of the Japanese government focused on the interests of Japan's military victory, so the various exploitations in the process of policy implementation still caused deep trauma to the Indonesian nation.